2017
DOI: 10.1038/srep45237
|View full text |Cite
|
Sign up to set email alerts
|

The co-evolution of networks and prisoner’s dilemma game by considering sensitivity and visibility

Abstract: Strategies adopted by individuals in a social network significantly impact the network, and they strongly affect relationships between individuals in the network. Links between individuals also heavily influence their levels of cooperation. Taking into account the evolution of each individual’s connection, we explore how sensitivity and visibility affect the prisoner’s dilemma game. The so-called ‘sensitivity’ and ‘visibility’ respectively present one’s self-protection consciousness and the ability of gaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Studies on weighted networks have attracted much attention as such networks enable the representation of the strength of each connection, which is essential information in a wide range of real-world scenarios including biological networks and social media. Recently, both the Prisoner's Dilemma and the Optional Prisoner's Dilemma games have been explored in the context of dynamic weighted networks, which lead to a coevolutionary scenario where not only the game strategies, but also the link weights, evolve over time [32,33,34,35,36]. Moreover, it has been shown that the use of dynamic weighted networks can increase heterogeneity of states (i.e., the number of possible utilities in the network), which in turn induces the promotion of cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on weighted networks have attracted much attention as such networks enable the representation of the strength of each connection, which is essential information in a wide range of real-world scenarios including biological networks and social media. Recently, both the Prisoner's Dilemma and the Optional Prisoner's Dilemma games have been explored in the context of dynamic weighted networks, which lead to a coevolutionary scenario where not only the game strategies, but also the link weights, evolve over time [32,33,34,35,36]. Moreover, it has been shown that the use of dynamic weighted networks can increase heterogeneity of states (i.e., the number of possible utilities in the network), which in turn induces the promotion of cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Optional participation is known to relax social dilemmas when a baseline payoff is granted to loners, 11,26 whereas link disconnection has been recently considered. 27 Our link inhibition is temporary and grants no profit to C's. We prefer abstention rather than forcing retaliation-cooperators defecting neighboring exploiters-because this is more connatural to the C mood.…”
Section: /12mentioning
confidence: 97%
“…Reciprocity is implemented by allowing C's to selectively abstain from playing for a few game rounds with exploiting neighbors. 11,26,27 So doing, C's reduce exploitation risks-with respect to unconditional C's-and, at the same time, communicate their mood, thus increasing their chances to reciprocate cooperation in future interactions. We name this new mechanism for the social evolution of cooperation networked rational reciprocity.…”
Section: Introductionmentioning
confidence: 99%
“…Como se puede apreciar, si los jugadores deciden cooperar entre ellos, van a obtener una recompensa (R), pero, si un jugador decide cooperar y el otro lo traiciona, quien coopera obtendrá en pago del bobo (S) y el traidor mayor pago dentro del juego (T) (Li, Ma, Mei , Tian, & Stanley, 2017) considerando esto, la solución clásica del dilema del prisionero se da cuando los jugadores deciden no cooperar obteniendo un pago P. Si bien es cierto, y como ya se expuso con anterioridad, la cooperación entre las partes (pago R) es, en un sentido empírico, la actitud estratégica más conveniente para los jugadores, considerando que R>P.…”
Section: Considerando Que T > R > P > Sunclassified